The Role of Madrasah Diniyah Takmiliyah Awaliyah (Mdta) Al-Furqon in Improving Al-Qur'an Reading and Writing Literacy for Students in Pematangsiantar - Ayuni, Audy; Ritonga , Asnil Aidah (Journal of Educational Sciences, 2025)
The improvement of reading and writing literacy of the Al-Qur'an among students is an important aspect of religious education in Indonesia, especially at the level of Madrasah Diniyah Takmiliyah Awaliyah (MDTA). This research aims to analyze the role of Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Al-Furqon in enhancing the reading and writing literacy of the Al-Qur'an (BTQ) for students in Pematangsiantar. This study uses a qualitative approach with a phenomenological method. Data collection techniques were carried out through observation, interviews, and documentation, which were then analyzed using the Miles and Huberman model. The results show that MDTA Al-Furqon has a significant role in improving the ability to read tartil, understand the basics of tajwid, and write letters and verses of the Al-Qur'an. Overall, the existence of MDTA Al-Furqon has a real positive impact in supporting the strengthening of Quranic literacy from an early age, which serves as an important foundation in the formation of faith, morality, and love for the Quran among the youth. This research contributes significantly to the development of a holistic, accessible, and relevant non-formal Islamic education model that meets the community's needs.